The 5.8 µm absorption bands for nitric acid (H14N16O3): line positions and intensities for the ν2 band at 1709.567 cm−1 and for its first associated hot bands (ν2+ν9−ν9, ν2+ν7−ν7, ν2+ν6−ν6). (18th August 2022) - Perrin, A.; Manceron, L.; Armante, R.; Kwabia-Tchana, F.; Roy, P.; Doizi, D.; Toon, G.C.
Abstract : This paper is the second of two back-to-back works, whose goal was to generate a more accurate linelist for the 5.8 µm absorption band of HNO3 . Here, we report improved line positions and intensities in the ν2 cold band which is the main band in this region. For this, we recorded four high-resolution Fourier transform spectra for the ν2 band, centered at 1709.567 cm −1, under different experimental conditions. Using these spectra, a new extended line position analysis was performed for the ν2 band, leading to more accurate line positions. In parallel, individual line intensities were measured. It appears that, although the ν2 band is mainly of B-type, it also possesses a (very) weak A-type component that cannot be ignored. Overall, the line intensities in this new database are about 8% weaker than those quoted presently in the HITRAN (https://hitran.org/ ) or GEISA (https://geisa.aeris-data.fr/ ) databases. Our final linelist for HNO3 at 5.8 µm is provided as a supplement to this paper. It includes lines from the ν2 band together with those of the ν2 +ν9 −ν9, ν2 +ν6 −ν6, and ν2 +ν7 −ν7 associated hot bands that were generated during the first part of this study, described in the companion paper. GRAPHICAL ABSTRACT: UF0001